Draft Genome Sequence of the Moderately Halophilic Bacterium Pseudoalteromonas ruthenica Strain CP76 - de la Haba, Rafael R. (American Society for Microbiology, 2013)
Pseudoalteromonas ruthenica strain CP76, isolated from a saltern in Spain, is a moderately halophilic bacterium belonging to the Gammaproteobacteria. Here we report the draft genome sequence, which consists of a 4.0-Mb chromosome, of this strain, which is able to produce the extracellular enzyme haloprotease CPI.